Pandemic Vocabulary and Its Equivalents in Short Story “Cerita Saat Jeda”: Literature as Literacy Teaching Materials - Ramis Rauf; Afriani Ulya; Sulmi Magfirah (Jurnal Sinestesia, 2023)
A pandemic or global epidemic is a disease transmitted simultaneously throughout the world. In 2019, the world faced a global outbreak of Covid-19. As a result, all lifelines have been paralyzed, starting from access to education, the economy, and health. However, there is a common thread from the event. One of them is the contribution of some vocabulary or foreign language terms. This paper aims to present some pandemic vocabulary and its equivalents through the collection of short stories “Cerita Saat Jeda” by Kaizen Writing Alumni Dee Lestari. The problem in this paper is formulated in the form of a question, “What is the English pandemic vocabulary narrated in the collection of short stories “Cerita Saat Jeda"? To answer these problems, the article uses the literary criticism approach of M.H. Abrams "the mirror and the lamp." According to Abrams, literature has three functions, namely, as a mirror, as a lamp, and as a medium. The research results show that the Covid-19 pandemic positively impacts society by producing new vocabulary or terms through literary works. The pandemic has become the new Indonesian language vocabulary in the Kamus Besar Bahasa Indonesia (KBBI).